STUDENTS SELF-ASSESSMENT ON WEB-BASED GRAMMAR EXERCISES DURING COVID-19 PANDEMIC - Latifah, Latifah (Universitas Pamulang, 2022)
The higher education community got significant challenges due to the raised of the Covid-19 pandemic around the globe. A full teaching and learning online has to be taken as the urgent alternation of the face-to-face university courses. Therefore, this research points at describing the advantages of using web-based learning and the students’ perceptions towards the techniques used. Furthermore, this research also aims to know the students ability to do self-assessment by using web-based exercises. The students’ grammar understanding would also be described in this research. Descriptive design was applied as the method to describe the students’ self-assessment in grammar web-based exercise. The data taken are quantitative and qualitative. Students’ perceptions are taken as qualitative data and the students’ grammar achievements are taken as the quantitative data. Thirty students of Advanced Grammar class are chosen as the data source. There are two instruments used in this research. They are the students’ grammar scores from web-based exercise and the questionnaire of students’ perception in grammar web-based exercise. The data are collected after the grammar class term ended. The research found that there are 55% of the students with their grammar mastery for the first half semester. However, there are 82, 8% of students that have a learning grammar mastery at the second half semester. It indicates that using web-based grammar exercise in teaching grammar can improve students’ achievement and mastery in learning grammar.